SISTEM PENDUKUNG KEPUTUSAN PENENTUAN JURUSAN DENGAN METODE MULTI FACTORY EVALUATION PROCESS (MFEP) (STUDI KASUS : SMK CIBENING) - Abdul Aziz Muhidin; Endra Suseno; Sugeng Supriyadi (FKOM UNIKU, 2019)
Smk Cibening is one of the schools in Cibingbin village, Cibingbin District, Kuningan Regency. The process of this course is intended so that the students can complete the school according to their abilities before continuing to a higher level, namely college. The current process of majors has disadvantages including the unavailability of special application to support courtesy, in helping counseling teachers to determine the right direction, so that the process takes a long time and also can occur a lot of consideration. to help the teachers in determining the majors of students at SMK Cibening. This study uses the Multifactor Evaluation Process (MFEP) method. The criterias used are report cards, national examination results (SKHUN) and majors. The final results of this study found that the decision support system with the Multifactor Evaluation Process (MFEP) method is able to overcome the problems in the process of determining the majors at SMK Cibening.Keywords: decision support system, WATERFALLl, with Multifactor Evaluation Process (MFEP) Method